2020
DOI: 10.1038/s41598-020-57772-7
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative cooperativity of TNF and Interferon-γ in regulating synovial fibroblast function and B cell survival in fibroblast/B cell co-cultures

Abstract: Synovial fibroblasts (SF) were reported to produce B cell activating factor (BAFF) in response to stimulation with interferon-γ (IFN-γ) or tumor necrosis factor (TNF). However, the influence of these pro-inflammatory cytokines on other receptors/ligands of the TNF superfamily or associated cytokine receptors in SF has not been investigated yet. Here we show the differential regulation of BAFF (CD257), Fn14 (CD266), TACI (CD267), BAFF-R (CD268), BCMA (CD269), CD40 ligand (CD40L, CD154), IFN-γR (CD119), Leptin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…This occurs in a BAFF dependent manner and requires direct contact between FLS and B cells. FLS express the membrane bound form of BAFF following stimulation with IFN-γ/TNF-α and promote B cell survival[163]. A study by Francois et al, found that contact between SSc dermal fibroblasts and B cells promoted collagen production, however SSc fibroblasts did not secrete BAFF or express the BAFF receptor[6].…”
mentioning
confidence: 99%
“…This occurs in a BAFF dependent manner and requires direct contact between FLS and B cells. FLS express the membrane bound form of BAFF following stimulation with IFN-γ/TNF-α and promote B cell survival[163]. A study by Francois et al, found that contact between SSc dermal fibroblasts and B cells promoted collagen production, however SSc fibroblasts did not secrete BAFF or express the BAFF receptor[6].…”
mentioning
confidence: 99%
“…In TAO patients' retrobulbar space, elevated VCAM-1 in endothelial cells has been detected to induce the recruitment of lymphocytes (Heufelder and Scriba, 1996). Except for endothelial cells, fibroblasts can express VCAM-1 in response to TNF-a, which has been proved in autoimmune rheumatoid arthritis (Lowin et al, 2020). In TAO patients, VCAM-1 can also be elevated by activated immune cells, such as Th17 cells, and mediates orbital fibrosis and adipogenesis (Fang et al, 2017(Fang et al, , 2021.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, IFN-γ overproduction is involved in cancer progression by stimulating tumour growth with immunoevasive properties [ 94 ]. This pro-oncogenic property of IFN-γ is probably due to its ability to regulate B cell-activating factor, BAFF production [ 95 , 96 ], a cytokine involved in B cell survival and differentiation. Increased production of BAFF was observed in SLE, particularly in the pathogenesis of lupus nephritis, causing an overproduction of T cell-dependent B cell pathogenic autoantibodies [ 95 , 97 ].…”
Section: Deregulation Of Rhoh In Diseasesmentioning
confidence: 99%